2015
DOI: 10.1038/nrc3895
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A in haematological malignancies

Abstract: DNA methylation patterns are disrupted in various malignancies, suggesting a role in the development of cancer, but genetic aberrations directly linking the DNA methylation machinery to malignancies were rarely observed, so this association remained largely correlative. Recently, however, mutations in the gene encoding DNA methyltransferase 3A (DNMT3A) were reported in patients with acute myeloid leukaemia (AML), and subsequently in patients with various other haematological malignancies, pointing to DNMT3A as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
344
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 405 publications
(356 citation statements)
references
References 167 publications
(244 reference statements)
11
344
1
Order By: Relevance
“…7B). Consistent with the published observation that dif- (4,24,25), we found that an intergenic region in the proximity of the Iqgap2 locus was substantially hypomethylated in KO cells (Fig. 7B).…”
Section: Dysregulated Dna Methylation Activity Leads To Increased Massupporting
confidence: 92%
See 4 more Smart Citations
“…7B). Consistent with the published observation that dif- (4,24,25), we found that an intergenic region in the proximity of the Iqgap2 locus was substantially hypomethylated in KO cells (Fig. 7B).…”
Section: Dysregulated Dna Methylation Activity Leads To Increased Massupporting
confidence: 92%
“…S1D). Second, the differentially methylated regions identified in Dnmt3a-null cells showed substantial hyper-as well as hypomethylation at a variety of genomic regions, with very little correlation between changes in methylation and differential gene expression in the absence of Dnmt3a in both mouse and human cells (4,24,25). These observations suggest the existence of both direct and indirect effects due to the loss of Dnmt3a, and potentially also the existence of DNMT3A activities that are independent of its DNA catalytic activity (26), similar to what has been described for the catalytically inactive DNMT3L (27), some of the DNMT3B isoforms (28), and even for the TET family of DNA-modifying enzymes (29,30).…”
Section: Dysregulated Dna Methylation Activity Leads To Increased Masmentioning
confidence: 99%
See 3 more Smart Citations